Swing and a hit : nine innings of what baseball taught me - O'Neill, Paul, 1963-; Curry, Jack (Twelve, 2022)
The five-time World Series champion and five-time All-Star elaborates on his most important hitting principles, lessons, and memories, providing constant insights into the beauty and frustration of playing baseball.